A Life of "Continuous and Honourable Usefulness:" Chemical Consulting and the Career of Robert Warington (1807-1867). (2nd July 2020) - Simmons, Anna
Abstract : Robert Warington (1807-1867) was a central figure in the mid-nineteenth century chemical community, notably through his role in the foundation of the Chemical Society of London in 1841. As demand for chemical services grew, Warington constructed an ultimately lucrative career in chemistry in which consulting played a major part. His formative years laid ideal foundations for establishing himself as a consultant, whilst his appointment as chemical operator to the Society of Apothecaries' pharmaceutical trade provided the status and infrastructure to sustain this activity. Here I explore the nature of the chemical services he performed for a range of customers through a survey of his experimental notes. At a time when professional boundaries in the subject were being delineated, this case study provides an example of how chemistry could be commercialised outside the academic environment and how consulting merged into a broader scientific career.